High-yielding and chemically enriched maize hybrids bred in Serbia – the best basis for super quality feed and food - Radenović, Čedomir N.; Delić, Nenad S.; Radosavljević, Milica M.; Jovanović, Života V.; Sečanski, Mile D.; Popović, Aleksandar S.; Crevar, Miloš S.; Radosavljević, Nebojša D. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: This paper presents the results of several different research studies. The inbred lines ZPPL 146 and ZPPL 159 and the maize hybrids ZP 633, ZP 735, and ZP 737 are primarily intended for human and livestock nutrition. Their selection took about four decades.Methods:  Spectral bands were registered using the method of resonant Raman spectroscopy of the leaves of inbred maize lines. These spectral bands indicate the conformational characteristics of not only carotenoid molecules but also other compounds (phosphate, gluten, and amide III) in the leaf.Results: A systematic examination of the inbred lines ZPPL 146 and ZPPL 159 and their maize hybrids ZP 633, ZP 735, and ZP 737 was performed in this paper. It was stated that the new inbred lines of corn, i.e. ZPPL 146 and ZPPL 159, are rich in carotenoids and yellow pigments. These lines also have significant quantities of other valuable bioactive compounds and good physical characteristics. The lines have an upright position of the top leaves and belong to the group of maize lines with significant characteristics of the photosynthetic model. They are resistant to high temperatures and are drought tolerant.Conclusion: This paper presents the relevant properties, characteristics and parameters of the new studied inbred maize lines that can be used in selection processes in the future. High-yielding and high-quality maize hybrids, i.e. ZP 633, ZP 735, and ZP 737, have been created from the mentioned inbred maize lines. They are recognizable by their qualities. The hybrid ZP633 is especially noteworthy for human consumption (children and the elderly). Further, from the agronomic-veterinary point of view, it is confirmed that the hybrids ZP 735 and ZP 737 are the most suitable for livestock feeding with the programmed use of corn silage. The relevant agronomic, morphological and nutritional properties of the maize hybrids ZP 633, ZP 735, and ZP 737 are also presented in this paper. The results regarding the grain structure and yield height for grain and silage for the hybrids ZP 677 and ZP 684, produced in Serbia and the countries of Southeastern Europe, are also given.
Keywords: Delayed chlorophyll fluorescence; Raman spectroscopy of leaves; photosynthetic model; Zea mays L; inbred lines; hybrids; thylakoid membrane; pigment properties; nutritive values; good quality food and feed